Toxic Parenting in “My Papa’s Waltz” By Theodore Roethke - Andini Dwi Wardani (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2023)
This study investigates toxic parenting portrayed in Theodore Roethke’s poem, “My Papa’s Waltz”, by applying the Reader-response theory. This poem is chosen due to its lines that portray toxic parenting. This study is descriptive qualitative research, so this study focuses on words rather than numbers. The data source is Theodore Roethke’s poem, “My Papa’s Waltz”. The result shows that there is evidence of toxic parenting in “My Papa’s Waltz” such as the father having more power in the family than the mother, the father feeling frustrated and easily emotional, and the son does not have the power to stand out for his rights. The researchers also find the reason why his parents become toxic. Then the researchers apply reader-response theory to analyze in deep regarding the findings. This study concludes that toxic parenting has influenced children’s psychology. It is due to that parents play an important role in encouraging children's early learning